Serangan hama invasif Spodoptera frugiperda (J. E. Smith) (Lepidoptera: Noctuidae) pada tanaman jagung di Kabupaten Ende Flores, Indonesia - Yustina MSW Pu'u; Charly Mutiara (Jurnal Entomologi Indonesia, 2021)
Corn is the main commodity in Ende Regency. One of the obstacles faced by farmers at the end of 2019 was the attack of the armyworm Spodoptera frugiperda (J. E. Smith) (Lepidoptera: Noctuidae) which is an invasive pest. Information about its spread in Flores are lacking. Therefore the aim of this research is to conduct a survey on the geographic distribution of S. frugiperda during the growing season of June–July 2020 in Flores, its infestation, and the presence of natural enemies. Observations were made on 200 sample plants in each of the 5 location. Calculations were made on the population level and intensity of attack. The intensity of the attack was measured using the Davis scale. The results showed that the pest population and attack intensity of S. frugiperda in the Rewarangga village was 8.15 individuals/plant and 76%, Lokoboko was 1.32 individuals/plant and 34%, Nanganesa was 2.48 individuals/plant and 51%, Rewarangga amounted to 5.96 individuals/plant and 55%, and Borokanda 3.31 individuals/plant and 42%. The natural enemies of S. frugiperda have not been found in the field.